Energy access scenarios to 2030 for the power sector in Sub-Saharan Africa - Morgan Bazilian; Patrick Nussbaumer; Hans-Holger Rogner; Abeeku Brew-Hammond; Vivien Foster; Shonali Pachauri; Eric Williams; Mark Howells; Philippe Niyongabo; Lawrence Musaba; Brian Ó Gallachóir; Mark Radka; et al. (Fondazione Eni Enrico Mattei (FEEM), 2011)
In order to reach a goal of universal access to modern energy services in Africa by 2030, consideration of various electricity sector pathways is required to help inform policy-makers and investors, and help guide power system design. To that end, and building on existing tools and analysis, we present several high-level, transparent, and economy-wide scenarios for the sub-Saharan African power sector to 2030. We construct these simple scenarios against the backdrop of historical trends and various interpretations of universal access. They are designed to provide the international community with an indication of the overall scale of the effort required. We find that most existing projections, using typical long-term forecasting methods for power planning, show roughly a threefold increase in installed generation capacity occurring by 2030, but more than a tenfold increase would likely be required to provide for full access - even at relatively modest levels of electricity consumption. This equates to approximately a 13% average annual growth rate, compared to a historical one (in the last two decades) of 1.7%.
Keywords: C1; Q41; Q47; 330; Energy Access; Power System Planning; Sub-Saharan Africa